Respon Penerimaan Gula Stevia Sebagai Pengganti Gula Tebu dan Gula JawaPada Proses Pengolahan Tradisional Kunyit Asam - Lucky Damayanti; Triadinda Yudha Wardani; Chrystia Aji Putra (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Traditional herbal medicine is one of the health drinks that exist and come from many enthusiasts. Herbal drink is an ancestral heritage recipe for the people of Indonesia which is still preserved and developed to this day. The ingredients used in making herbal medicine are herbal plants that can be found in the surrounding environment. This research was conducted using a quasi-experimental design method. The results of the organoleptic test of traditional herbal medicine with the addition of 30 grams of palm sugar resulted in an average respondent's answer, namely having the aroma of turmeric, Javanese sugar, sweet taste, dark yellow color, and a liquid texture. Stevia Sugar The results of the organoleptic test of herbal medicine with the addition of traditional stevia sugar as much as 30gr have results with - the average respondent's answer is that it has a taste like tea leaves, sweet taste tends to be bitter, dark brown in color, and has a thick texture. From the results of this study, it can be seen that the addition of stevia sugar to the sour turmeric herbal medicine is considered ineffective. The addition of palm sugar to the traditional herbal medicine turmeric acid is considered more effective.